2020
DOI: 10.3389/fncel.2020.600280
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of High Mobility Group Box 1 in Cerebral Ischemic Injury

Abstract: High mobility group box 1 (HMGB1) is a ubiquitous nuclear protein that plays an important role in stabilizing nucleosomes and DNA repair. HMGB1 can be passively released from necrotic neurons or actively secreted by microglia, macrophages/monocytes, and neutrophils. Cerebral ischemia is a major cause of mortality and disability worldwide, and its outcome depends on the number of neurons dying due to hypoxia in the ischemic area. HMGB1 contributes to the pathogenesis of cerebral ischemia via mediating neuroinfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 131 publications
(191 reference statements)
1
26
0
Order By: Relevance
“…Apart from the anti-oxidative property of OI, inhibition of inflammation is pivotal in alleviating liver injury. HMGB1 is a nuclear protein that can be translocated to the extracellular milieu under certain stimuli, such as necrosis and inflammation ( Gou et al, 2020 ). HMGB1 plays important roles in inflammation diseases such as sepsis and acute liver injury ( Chen et al, 2014 ; Gaskell et al, 2018 ; Deng et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the anti-oxidative property of OI, inhibition of inflammation is pivotal in alleviating liver injury. HMGB1 is a nuclear protein that can be translocated to the extracellular milieu under certain stimuli, such as necrosis and inflammation ( Gou et al, 2020 ). HMGB1 plays important roles in inflammation diseases such as sepsis and acute liver injury ( Chen et al, 2014 ; Gaskell et al, 2018 ; Deng et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that silencing TUG1 could increase the viability of hippocampal neurons and inhibit their apoptosis. Interestingly, in a model of Alzheimer’s disease, TUG1 silencing can increase neuron cell survival and inhibit apoptosis of hippocampal neurons [ 25 ]. The findings were consistent with our research results.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular HMGB1 mostly interacts with TLR2 and TLR4 to provoke inflammatory responses via the NF-kB pathway [ 56 ]. HMGB1 is a target for therapeutic approaches to various cancers and may play a role in the treatment of CVDs [ 57 , 58 ].…”
Section: General Aspects Of Tlr Signaling Pathwaysmentioning
confidence: 99%